The effect of colposcopy counseling with a feminist model on anxiety in Thai women with abnormal cervical cytology results: A time-series quasi-experimental study - Sarwitree Pornsinsiriruck; Bualuang Sumdaengrit; Suvimol Kongrot; Ketkaew Jengprasert; Noppamat Puntusopon (Belitung Nursing Journal, 2023)
Background: Due to the cervical cancer screening campaign, there is a gradual increase in the number of women diagnosed with abnormal cervical cytology results. Most women experience high anxiety upon learning about these results, leading to adverse psychological effects. Therefore, nurses play a vital role in counseling these women to alleviate their concerns. Objective: This study aimed to examine the effect of colposcopy counseling with a feminist model on anxiety in Thai women with abnormal cervical cytology results. Methods: The study employed a time-series quasi-experimental design with a comparison group. It was conducted at the colposcopy clinic of a university hospital in Bangkok, Thailand, from August 2022 to April 2023. A total of 68 women with abnormal cervical cytology results were purposively recruited based on inclusion criteria. The comparison group (n = 34) received only usual care, while the experimental group (n = 34) received colposcopy counseling and usual care. Colposcopy counseling was provided after collecting baseline data. Anxiety was assessed at baseline, immediate post-test, and 12th week post-test. Data were analyzed using descriptive statistics, Chi-square test, independent t-test, and repeated measures analysis of variance (ANOVA). Results: There was no statistically significant difference in anxiety across the three-time points between the two groups (F1, 66 = 0.062, p = 0.804). However, anxiety in the experimental group significantly decreased over time (p <0.05). In contrast, anxiety in the comparison group at baseline was not significantly different from that at the immediate post-test (p = 0.480). Conclusion: Colposcopy counseling was effective in reducing anxiety in Thai women with abnormal cervical cytology results, especially during the initial period after receiving the results. Nonetheless, anxiety could gradually decrease regardless of the intervention. Therefore, colposcopy counseling by nurses and healthcare providers is helpful for women in relieving anxiety during their first colposcopy attendance.